2020
DOI: 10.1155/2020/2807120
|View full text |Cite|
|
Sign up to set email alerts
|

Beta-Thalassemia Intermedia: A Single Thalassemia Center Experience from Northeastern Iraq

Abstract: Objective. To determine the molecular characterization and disease-associated complications of beta-thalassemia intermedia (β-TI) patients in Sulaymaniyah province, northeastern Iraq. Methods. A total of 159 β-TI patients from 114 families were enrolled. Detection of β-thalassemia mutations was done by reverse hybridization technique and direct gene sequencing. Also, the clinical and hematological data were collected through an electronic-based medical recording system using a designed comprehensive questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…This result agree with (Ali and Abdulla., 2020) who found that male recorded 94(54%) and 81(46%) were females with a ratio 1.2: 1and mean age of patients were (10.5 ±5.8 years) , the range age of patients from 5 months to 34 years and found that more than half (55%) between aged 1 -10 years. In study by Amin et al, (2020)confirmed that male more susceptible to β-thalassemia disease with frequency 56.6% males and 43.4% females, with ratio male : female ratio of 1.3 : 1. The patients' ages ranged between 1.4 -54 years with a median of 15 yrs.…”
Section: Demographic Study Distribution Of Study Subjects According T...mentioning
confidence: 87%
“…This result agree with (Ali and Abdulla., 2020) who found that male recorded 94(54%) and 81(46%) were females with a ratio 1.2: 1and mean age of patients were (10.5 ±5.8 years) , the range age of patients from 5 months to 34 years and found that more than half (55%) between aged 1 -10 years. In study by Amin et al, (2020)confirmed that male more susceptible to β-thalassemia disease with frequency 56.6% males and 43.4% females, with ratio male : female ratio of 1.3 : 1. The patients' ages ranged between 1.4 -54 years with a median of 15 yrs.…”
Section: Demographic Study Distribution Of Study Subjects According T...mentioning
confidence: 87%
“…Although the spectrum of β-thal mutations in the Arab region is highly diversified and mostly shared with other ethnic groups, we identified six HBB gene mutations that our search strategy identified as unique to Arabs ( Table 1) is associated with both β-thal intermedia and major in Iran [61], as well as in Saudi Arabia and Palestine [52,51], while it causes β-thal major in United Arab Emirates, Syria, Lebanon, Algeria and Qatar [54,59,50,53,45], and it is linked with β-thal intermedia in Iraq and Kuwait [21,55]. The c.27dupG is associated with β-thal major in Saudi, Syria, Qatar [58,22,45], while in Iraq it causes β-thal intermedia and it is associated with both β-thal intermedia and major in Palestine, Egypt [44,23].…”
Section: Unique Mutations In Arabsmentioning
confidence: 99%
“…It also shows that the bulk of the mutations was Mediterranean, with some Turkish, Kurdish, Saudi Arabian, Azerbaijani, and Asian Indian origins. A further 15 mutations were reported infrequently or sporadically (< 1.0%) that include codon 36/37 (−T), IVS-I-130 (G>C), IVS-II-745 (C>G), IVS-II-850 (G>T), codon 22 (−7 bp), codon 30 (G>C), codon 15 (G>A), codon 127 (CAG>CGG), − 101 (C>T), − 87 (C>G), − 30 (T>A), − 28 (A>C), poly-A (AATAAA>AATAAG), 5′ UTR + 22 (G>A), and CAP + 1(A>C) (Al-Allawi et al 2010a, 2014Amin et al 2020;Jalal et al 2010;Shamoon et al 2015). The spectrum of mutations noted among Kurds is quite consistent with their history and interactions with surrounding Mediterranean populations, while the presence of Asian Indian mutations could be attributed to the region being along the ancient silk road route, which connected China and Europe through the Indian subcontinent and the Middle East.…”
Section: Molecular Basis Of β-Thalassemia Among Kurdsmentioning
confidence: 99%